2015
DOI: 10.3892/or.2015.3886
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin in prostate cancer: Chemotherapeutic and chemopreventive effects, mechanisms and clinical application potential (Review)

Abstract: The morbidity and mortality of prostate cancer have been increasing recently, and the comprehensive treatment for prostate cancer is unable to achieve satisfactory outcomes. Quercetin is a natural flavonoid compound that has attracted increased interest and attention due to its anticancer activity. In vitro and in vivo studies have verified that quercetin effectively inhibits prostate cancer via various mechanisms. Clinical trails concerning the pharmacokinetics and application of quercetin in humans have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 105 publications
1
70
0
Order By: Relevance
“…[4546] Both in vitro and in vivo cancer studies, quercetin was said to have a beneficial effect against prostate cancer. [47]…”
Section: Introductionmentioning
confidence: 99%
“…[4546] Both in vitro and in vivo cancer studies, quercetin was said to have a beneficial effect against prostate cancer. [47]…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vivo animal experiments and in vitro studies exhibited wide range of pharmacological activities of quercetin, kaempferol and their glycosides [42][43][44][45]. The main issue concerning utilization of these flavonols is low bioavailability and stability.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, several studies have shown the effectiveness of different novel natural compounds against different cancers. Quercetin was effective against prostate cancer by blocking several key survival pathways (Yang et al, ). Curcumin, a well‐known constituent of turmeric, is being evaluated for its effectiveness against several cancers including brain cancer, breast cancer, lung cancer, and prostate cancer (Ravindran, Prasad, & Aggarwal, ).…”
Section: Natural Products In Anticancer Therapy: Benefits and Challengesmentioning
confidence: 99%
“…Researchers also explored microbes and the marine organism as a source of natural compounds (Discovery, ). Nature‐derived compounds have various pharmacological activities including antiangiogenic (Sulaiman, Basavarajappa, & Corson, ), antiprotozoal (Jones, Grkovic, Sykes, & Avery, ; Singh, Mishra, Bajpai, Singh, & Tiwari, ), antiatherosclerotic (Orekhov, Sobenin, Revin, & Bobryshev, ), antimicrobial (Farha & Brown, ; Genilloud, ), anti‐obesity (Fu, Jiang, Guo, & Su, ), antioxidant (Fiedor & Burda, ), antidiabetic (Nazaruk & Borzym‐Kluczyk, ), hepatoprotective (Madrigal‐Santillán, ), anti‐inflammatory (Arulselvan et al, ), neuroprotective (Ebrahimi & Schluesener, ; Essa et al, ), and chemotherapeutic (Amin et al, ; Sznarkowska, Kostecka, Meller, & Bielawski, ; Yang et al, ) effects.…”
Section: Introductionmentioning
confidence: 99%